DRY EXTRACT OF SCUTELLARIA BAICALENSIS GEORGI HEPATOPROTECTIVE ACTION IN VANCOMYCIN IMPLEMENTATION - A. A. Potapova; E. G. Dorkina; A. Yu. Terekhov; E. O. Sergeeva; L. A. Sadzhaya (Фармация и фармакология (Пятигорск), 2015)
During experiments with rats we have studied a dry extract of Scutellaria baicalensis georgi and carsil in vancomycin use. We have shown that vancomicyn use causes toxical damage of lever. We have experimentally proved the prospects of creation based on the dry extract of Scutellaria baicalensis georgi - preparation for hepatotoxical action of vancomycin correction